KMOS: A multi-object deployable-IFU spectrometer for the ESO VLT - Sharples, R; Bender, R; Bennett, R; Burch, K; Carter, P; Clark, P; Content, R; Davies, R; Davies, R; Dubbeldam, M; Genzel, R; Hess, A; et al. (2006)
We describe the design of a 2nd generation instrument for the ESO VLT which uses 24 cryogenic pickoff arms linked to diamond-machined image slicing integral field units to deliver a unique multiple deployable integral field capability in the near-infrared (1-2.5 mu m). The science requirements for the instrument are presented and linked to the functional specification. The baseline instrument concept is described with emphasis on technological innovations. (c) 2006 Elsevier B.V. All rights reserved.